The topology of the generic polar curve and the Zariski invariant for branches of genus one - García Barroso Evelia R.; Hernandess Marcelo E.; Fernando Hernández Iglesias M. (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica)
We study, for plane complex branches of genus one, the topological type of its generic polar curve, as a function of the semigroup of values and the Zariski invariant of the branch. We improve some results given by Casas-Alvero in 2023, since we filter the topological type fixed for the branch by the possible values of Zariski invariants.